2002
DOI: 10.1007/s00425-002-0742-4
|View full text |Cite
|
Sign up to set email alerts
|

In situ localisation of cytokinins in the shoot apical meristem of Sinapis alba at floral transition

Abstract: In plants of Sinapis alba L. induced to flower by one long day (LD), previous work showed that the phloem sap feeding the shoot apex is enriched in cytokinins of the isopentenyladenine (iP)-type between 9 and 25 h after start of the LD [P. Lejeune et al. (1994) Physiol Plant 90:522-528]. We have checked the hypothesis that the cytokinin content of the shoot apical meristem (SAM) should increase in response to floral induction by one LD using histoimmunolocalisation techniques and rabbit antiserum against isope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…Although the reason for the difference between Arabidopsis and P. patens is unclear at present, our results indicate that the PDV levels are regulated by a cell differentiation system responsive to cytokinin. The highest expression of PDV proteins around the shoot apical meristem and young emerging leaves in Arabidopsis (Figure 2) is consistent with a previous observation that content of cytokinin is highest in meristems (Jacqmard et al, 2002). The induction of PDV expression by cytokinin might be related to the observation that cytokinin addition or expression of the ipt gene, whose product catalyzes the rate-limiting step in cytokinin synthesis, complements a P. patens mutant defective in chloroplast division (Reski et al, 1991;Reutter et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Although the reason for the difference between Arabidopsis and P. patens is unclear at present, our results indicate that the PDV levels are regulated by a cell differentiation system responsive to cytokinin. The highest expression of PDV proteins around the shoot apical meristem and young emerging leaves in Arabidopsis (Figure 2) is consistent with a previous observation that content of cytokinin is highest in meristems (Jacqmard et al, 2002). The induction of PDV expression by cytokinin might be related to the observation that cytokinin addition or expression of the ipt gene, whose product catalyzes the rate-limiting step in cytokinin synthesis, complements a P. patens mutant defective in chloroplast division (Reski et al, 1991;Reutter et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…In the same experimental system, it was also demonstrated that the inductive LD causes production in the leaves of a mobile signal, the "Xoral stimulus", which is S. Ormenese · G. Bernier · C. Périlleux (&) Laboratory of Plant Physiology, Department of Life Sciences, University of Liège, B22 Sart Tilman, 4000 Liege, Belgium e-mail: cperilleux@ulg.ac.be ultimately responsible for the promotion of the Xoral transition at the SAM (Bernier and Périlleux 2005). This stimulus was shown to be multifactorial and one of its components was identiWed as a cytokinin of the isopentenyladenine-type (Lejeune et al 1988(Lejeune et al , 1994Bernier et al 1993;Havelange et al 2000;Jacqmard et al 2002). Application of a cytokinin to the SAM of SD-grown (vegetative) S. alba plants was able to mimic almost perfectly some of the events that occur normally during the SAM Xoral transition, such as the increase in mitotic activity (Jacqmard et al 1998), the fragmentation of the vacuoles (Havelange et al 1986) and upregulation of the SaMADSA gene, the Sinapis homologue of the Arabidopsis SOC1 gene (Bonhomme et al 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Although Banno et al (2001) reported that DRN/ESR1 expression can be induced in root cultures, we did not detect DRN/ESR1 expression in roots of wild-type Arabidopsis seedlings. Because cytokinins are present throughout plant meristems and organs (Jacqmard et al, 2002), we regard it as unlikely that the complex and cell type-specific expression pattern of DRN is controlled mainly by cytokinin levels. Furthermore, we also showed that increased DRN/ESR1 expression represses STM in the meristem, whereas increased cytokinin signaling promotes the expression of STM and other homeobox genes (Rupp et al, 1999).…”
Section: Does Drn/esr1 Act In a Signaling Pathway That Controls Cell mentioning
confidence: 99%